Analysis of Students’ Proficiency in Writing Narrative Text - Asriati; Nuzulul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The skill of writing narrative texts is still very low and difficult for most students of SMPN 1 Kuala Batee. The objectives of this study are 1) to find out the level of students' ability in writing narrative texts, 2) to find out the causes that make their scores low in writing narrative texts. This study uses quantitative research. The subjects of the study were 98 students. The test is used as a data collection technique. The results of the study show that, there are 81 students who could not write narrative texts at all or were included in the Very Poor category, 6 students who got a category with a score range of 70-79. There are 4 students who are included in the Excellent category with the highest score of 95. Then, 2 students were included in the Poor category and 5 students were included in the Very Poor category. Among the 98 students, only 17 students took the narrative text writing test. And among the 17 students, only 59% (10 students) were able to do it. The cause of students' low scores in writing narrative texts was found to be not mastering English vocabulary which led them not participating in the survey. Also, limited knowledge in identifying the general structure and language of narrative text features was also a cause to students’ low achievement in writing narrative text.